Improving Industrially Relevant Phenotypic Traits by Engineering Chromosome Copy Number in Saccharomyces pastorianus - Gorter de Vries, Arthur R.; Knibbe, Ewout; van Roosmalen, Roderick; van den Broek, Marcel; de la Torre Cortés, Pilar; O’Herne, Stephanie F.; Vijverberg, Pascal A.; el Masoudi, Anissa; Brouwers, Nick; Pronk, Jack T.; Daran, Jean-Marc G. (Frontiers in Genetics, 2020)
The lager-brewing yeast Saccharomyces pastorianus is a hybrid between S. cerevisiae and S. eubayanus with an exceptional degree of aneuploidy. While chromosome copy number variation (CCNV) is present in many industrial Saccharomyces strains and has been linked to various industrially-relevant traits, its impact on the brewing performance of S. pastorianus remains elusive. Here we attempt to delete single copies of chromosomes which are relevant for the production of off-flavor compound diacetyl by centromere silencing. However, the engineered strains display CNV of multiple non-targeted chromosomes. We attribute this unintended CCNV to inherent instability and to a mutagenic effect of electroporation and of centromere-silencing. Regardless, the resulting strains displayed large phenotypic diversity. By growing centromere-silenced cells in repeated sequential batches in medium containing 10% ethanol, mutants with increased ethanol tolerance were obtained. By using CCNV mutagenesis by exposure to the mitotic inhibitor MBC, selection in the same set-up yielded even more tolerant mutants that would not classify as genetically modified organisms. These results show that CCNV of alloaneuploid S. pastorianus genomes is highly unstable, and that CCNV mutagenesis can generate broad diversity. Coupled to effective selection or screening, CCNV mutagenesis presents a potent tool for strain improvement.